Integrating supply chain risk management activities into sales and operations planning - Christian Kalla; Luiz Felipe Scavarda; Bernd Hellingrath (Review of Managerial Science, 2024)
Sales and operations planning (S&OP) became a relevant managerial topic for academics and practitioners with a growing literature body and implementation cases in the industry. However, S&OP has been analysed mostly in stable environments, with few implications for uncertain environments. With the current growing pressure to deal with unexpected changes in the business environment, the integration with supply chain risk management (SCRM) activities has been considered a promising direction for the next S&OP generation. Within this context, this paper aims to advance the theoretical understanding of the interrelationship between S&OP and SCRM under different contexts and provide a practical guidance for adapting S&OP in uncertain environments. This goal is achieved by combining literature-based insights, obtained through a rigorous systematic literature review of 77 studies from academic and grey literature, with empirical insights from interviews with 15 industry experts. The research leads to a novel S&OP framework for dealing with uncertain environments. It integrates SCRM activities into S&OP, applying contingency theory as a theoretical foundation to address the context-specific nature of S&OP. Moreover, it embraces a holistic view for S&OP from an integrated people-process-IT perspective, encompassing the involved actors, the process itself and its steps, and the adopted information systems. Additionally, research findings reveal the possibility for an additional process to cope better with uncertain environments, which can run in parallel with the regular S&OP process. It is characterised by a higher planning frequency and a lower planning horizon, resulting in a closer linkage with operational planning and execution.
Keywords: M1; D20; L2; 650; Tactical planning; Uncertainty; Contingency theory; S&OE